Peningkatan Keterampilan Menembak Bola Basket melalui Model Pembelajaran Kooperatif Berbasis Permainan pada Siswa SMP - Alitya Putra Maulidan; Lazuardy Akbar Fauzan; Ramadhan Arifin (Universitas Hamzanwadi, 2026)
This study aimed to analyze the effect of a game-based cooperative learning model on improving basketball shooting skills among class IX E students at SMP Negeri 1 Banjarbaru, measured through body position, ball handling, movement coordination, and shooting accuracy. This study employed a quantitative approach using a one-group pretest-posttest design. The sample consisted of 32 students selected through purposive sampling. “Data were collected using a basketball shooting skills test and analyzed through descriptive statistics, the Shapiro-Wilk normality test, Levene’s homogeneity test, the Wilcoxon Signed-Rank Test, and effect size calculation. The results showed that the mean shooting score increased from 72.03 in the pretest to 82.34 in the posttest. The Wilcoxon Signed-Rank Test yielded a Z value of -4.415 with an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05), indicating a significant effect of the game-based cooperative learning model on students’ basketball shooting skills. The effect size value was 0.78, which falls into the large effect category, indicating a strong practical impact of the intervention.” Therefore, the game-based cooperative learning model can be considered an effective strategy in physical education learning to improve basketball shooting skills, participation, cooperation, and learning motivation among junior high school students.